Economic growth, unemployment, poverty, and income inequality in Indonesia: Evidence from a simultaneous panel data approach - Nur Aisya Aurellia; Timbang Sirait (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Social welfare is an important indicator in assessing a country's socio-economic condition. High economic growth, such as that experienced in Indonesia, shows no evidence of prosperity because empirical evidence indicates unemployment, poverty, and income inequality. Indonesia still prioritizes high economic growth without adequately considering its inclusiveness. These indicate that existing development is not fully inclusive and sustainable. The objectives of this study explicitly account for endogeneity and bidirectional relationships among welfare indicators during the 2019–2023 period. The research method used in this study is a simultaneous panel data approach with two-stage least squares, because the previous discussions were still carried out in a single-equation (one-stage). The best model selected is FE2SLS with FGLS-SUR. The results show that there is a simultaneity between economic growth and unemployment, poverty, and income inequality, and there is only a one-way causality relationship between poverty and income inequality, where poverty affects income inequality but not vice versa. Capital and labor have a positive effect on economic growth. On the other hand, the dominance of the informal sector has a positive effect on unemployment. Meanwhile, the number of social assistance recipients has a negative effect on income inequality. This study provides policies on the strategy development that not only focus on increasing economic growth but also simultaneously alleviate those problems to support the achievement of the 2020-2024 RPJMN targets and SDGs. For the next studies, it can be expanded to the fiscal and monetary policies and doing in-depth regional analysis.